2015
DOI: 10.1095/biolreprod.114.126052
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an L-Amino Acid Oxidase in Equine Spermatozoa1

Abstract: This study demonstrates for the first time the presence of an L-amino acid oxidase (LAAO) enzyme in equine spermatozoa that is able to generate significant amounts of reactive oxygen species (ROS) and create a state of oxidative stress. RT-PCR analysis revealed that the mRNA for this enzyme was present in the equine testis and spermatozoa, while immunocytochemical studies demonstrated that the mature LAAO protein was located in the sperm head, particularly in the acrosomal and postacrosomal domains. Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 54 publications
(56 reference statements)
1
40
0
Order By: Relevance
“…Egg yolk contains sufficient quantities of free aromatic amino acids to activate L‐Amino acid oxidase, so significant ROS generation could ensue in the presence of sufficient numbers of dead spermatozoa in the immediate vicinity of this enzyme. Given the substantial numbers of non‐viable spermatozoa are frequently observed in cryostored samples, sufficient oxidative stress may be created via L‐Amino acid oxidase activity to compromise the functionality of live spermatozoa in the same ejaculate (Aitken, Naumovski, et al, ). Amino acid oxidases are not, however, major physiological drivers of sperm capacitation.…”
Section: Physiological Sources Of Ros In Spermatozoamentioning
confidence: 99%
“…Egg yolk contains sufficient quantities of free aromatic amino acids to activate L‐Amino acid oxidase, so significant ROS generation could ensue in the presence of sufficient numbers of dead spermatozoa in the immediate vicinity of this enzyme. Given the substantial numbers of non‐viable spermatozoa are frequently observed in cryostored samples, sufficient oxidative stress may be created via L‐Amino acid oxidase activity to compromise the functionality of live spermatozoa in the same ejaculate (Aitken, Naumovski, et al, ). Amino acid oxidases are not, however, major physiological drivers of sperm capacitation.…”
Section: Physiological Sources Of Ros In Spermatozoamentioning
confidence: 99%
“…While cells are under stress due the presence of snake venoms, the phenomenon of DNA damage is amplified multifold. In the same line of research, Aitken et al38 reported the generation of free oxygen species which leads to the state of oxidative stress by l -amino acid oxidase in equine spermatozoa. In addition, Park et al39 demonstrated that in neuroblastoma cells an increase in ROS due to treatment with snake venoms increases pro-apoptotic proteins including Bax, and there was a downregulation of anti-apoptotic Bcl-2 protein upon treatment with venom.…”
Section: Discussionmentioning
confidence: 91%
“…One of the earliest modifications of a destabilized/deteriorating plasma membrane is the switching of the phospholipid phosphatidylserine (PS) from the inner to the outer face of the membrane (Peña et al, 2003;Aitken et al, 2015), a process related to capacitation and/or apoptosis . Sperm capacitation, particularly in pigs, but also in other species, including human, is triggered by high levels of bicarbonate, which renders the plasma membrane more fluid and leads to the exteriorization of PS, particularly in the sperm head domain (Harrison and Gadella, 2005;Rodriguez-Martinez, 2007).…”
Section: The Earliest Signs Of Deteriorationmentioning
confidence: 99%
“…(Bull: Erickson et al, 2015;ram: Martí et al, 2008;stallion: Gallardo-Bolaños et al 2012;boar: Juarez et al, 2011). The markers can simply be remnants of the apoptosis during spermatogenesis (Shaha et al, 2010) showing which cells had escaped the process, but are still condemned to die post-ejaculation (Aitken and Baker, 2013;Aitken et al, 2015). In contrast to apoptosis, necrosis is an accidental cell death following severe cell stress, normally of external source, that either disrupt the functionality of the male genitalia or that directly harm sperm membranes integrity during or after ejaculation (Guthrie and Welch, 2005).…”
Section: What Is Behind the Loss Of Viability Of Ejaculated Sperm Apmentioning
confidence: 99%
See 1 more Smart Citation